Axonal regeneration after spinal cord injury: molecular mechanisms, regulatory pathways, and novel strategies - Elmalky, Mohammed Ibrahim; Alvarez-Bolado, Gonzalo; Younsi, Alexander; Skutella, Thomas (Biology, 2024)
Axonal regeneration in the spinal cord after traumatic injuries presents a challenge for researchers, primarily due to the nature of adult neurons and the inhibitory environment that obstructs neuronal regrowth. Here, we review current knowledge of the intricate network of molecular and cellular mechanisms that hinder axonal regeneration, with a focus on myelin-associated inhibitors (MAIs) and other inhibitory guidance molecules, as well as the pivotal pathways implicated in both inhibiting and facilitating axonal regrowth, such as PKA/AMP, PI3K/Akt/mTOR, and Trk, alongside the regulatory roles of neurotrophins and axonal guidance cues. We also examine current insights into gene therapy, tissue engineering, and pharmacological interventions that show promise in overcoming barriers to axonal regrowth.
Online veröffentlicht: 7. September 2024
Gesehen am 26.02.2025